High-conductivity main gate electrode silver paste and preparation method and application thereof
By using Bi-B-Zn-type and P-V-Zn-type glass materials, silver conductive materials and conductive polymers in the main gate electrode silver paste, and performing microwave-ultrasound combined treatment, the problem of insufficient conductivity of the main gate electrode silver paste in the prior art is solved, high conductivity and stability are achieved, and the demand for high-performance photovoltaic cells is met.
Patent Information
- Application Number
- CN202411965750.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The current main gate electrode silver paste conductivity cannot meet the needs of high-performance photovoltaic cells, especially in areas with high performance requirements, such as aerospace and military, and silver paste with poor conductivity cannot meet the application needs.
By reasonably designing the chemical composition of the main gate electrode silver paste, using Bi-B-Zn-based and P-V-Zn-based lead-free low-temperature molten glass materials, combined with silver conductive materials, silver alloy conductive materials, conductive polymers and organic additives, microwave-ultrasound combined treatment was performed to prepare a high-conductive main gate electrode silver paste.
The conductivity of the main gate electrode silver paste is improved, the stability and strength of the network structure are enhanced, the sintering characteristics and conductivity of the silver paste are improved, and the demand for high-performance photovoltaic cells can be met.
Smart Images

Figure CN119833200A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of solar cells, and in particular to a high-conductivity main grid electrode silver paste and a preparation method and application thereof. Background Art
[0002] Main grid electrode silver paste is a special conductive paste, mainly used for the production of grid lines of photovoltaic cells. In the manufacturing process of photovoltaic cells, the main grid silver paste is coated on the front of the cell to form a fine grid line structure, which is not only responsible for collecting current, but also plays a role in supporting and protecting the cell.
[0003] The main grid electrode silver paste is the key material responsible for collecting and transmitting current in photovoltaic cells. Its conductivity directly affects the current transmission efficiency, thereby affecting the photoelectric conversion efficiency of photovoltaic cells. With the continuous advancement of photovoltaic technology and the rapid development of the photovoltaic industry, the performance requirements for photovoltaic cells are getting higher and higher. The conductivity of existing main grid electrode silver paste cannot meet the needs of high-performance photovoltaic cells, thus limiting the development and application of photovoltaic cells. Especially in some fields with high requirements for photovoltaic cell performance, such as aerospace, military and other fields, the main grid electrode silver paste with poor conductivity will not be able to meet its application requirements. Summary of the invention
[0004] The present application provides a main gate electrode silver paste with high conductivity and a preparation method and application thereof, in order to solve the following technical problem: how to improve the conductivity of the main gate electrode silver paste.
[0005] In a first aspect, the present application provides a high-conductivity main gate electrode silver paste, which is composed of the following components by mass: 0.5 to 4 parts of glass material, 50 to 70 parts of silver conductive material, 10 to 30 parts of silver alloy conductive material, 1 to 3 parts of organic additive, 1 to 3 parts of conductive polymer, and 10 to 15 parts of organic carrier; wherein,
[0006] The glass material consists of a first glass material and a second glass material;
[0007] The first glass material is a Bi-B-Zn series lead-free low-temperature melting glass material;
[0008] The second glass material is a PV-Zn series lead-free low-temperature melting glass material.
[0009] Optionally, the mass ratio of the Bi-B-Zn series lead-free low-temperature melting glass material to the PV-Zn series lead-free low-temperature melting glass material is (2-4):1.
[0010] Optionally, in terms of molar percentage, the Bi-B-Zn based lead-free low-temperature melting glass material is composed of the following components: Bi2O3: 20-30 mol.%, B2O3: 40-50 mol.%, ZnO: 2-6 mol.%, SiO2: 2-6 mol.%, Al2O3: 1-5 mol.%, NaBr: 1-5 mol.%, SnO2: 1-5 mol.%, CdO: 1-5 mol.%.
[0011] Optionally, the PV-Zn-based lead-free low-temperature melting glass material consists of the following components, in molar percentage: H3PO4: 40-50 mol.%, V2O5: 5-10 mol%, ZnO: 20-30 mol.%, In2O3: 5-10 mol%, KCl: 1-5 mol.%, CaO: 1-5 mol.%, Ce2O3: 1-5 mol.%, Y2O3: 1-5 mol.%.
[0012] Optionally, the silver alloy conductive material is composed of silver-clad nickel, silver-clad tungsten and silver-clad copper, and the mass ratio of the silver-clad nickel, the silver-clad tungsten and the silver-clad copper is (1-5):(1-5):(1-5).
[0013] Optionally, the conductive polymer is composed of polyaniline, polypyrrole, polyethylene dioxythiophene and polystyrene sulfonic acid, and the mass ratio of the polyaniline, the polypyrrole, the polyethylene dioxythiophene and the polystyrene sulfonic acid is 1:(1-2):(2-4):(2-4).
[0014] Optionally, the organic additive includes at least one of the following: a dispersant, a thickener, a coupling agent, a surfactant, a leveling agent and a defoaming agent; wherein,
[0015] The dispersant is polyvinyl pyrrolidone;
[0016] The thickener is ethyl cellulose or nitrocellulose;
[0017] The coupling agent is a silane coupling agent;
[0018] The surfactant is lecithin;
[0019] The leveling agent is dibutyl phthalate;
[0020] The defoamer is an organosilicon defoamer.
[0021] In a second aspect, the present application provides a method for preparing a high-conductivity main gate electrode silver paste according to any one of the embodiments of the first aspect, the method comprising the following steps:
[0022] S1, melting a first glass material and a second glass material to form a first glass liquid and a second glass liquid respectively;
[0023] S2, drying the first glass liquid and the second glass liquid respectively, and then processing them into a first glass material and a second glass material by using a jet milling process;
[0024] S3, mixing the first glass material and the second glass material to obtain a glass material;
[0025] S4, mixing the glass material, the silver conductive material, the silver alloy conductive material, the organic additive and the organic carrier to obtain a blend;
[0026] S5, subjecting the blend to a microwave-ultrasound combined treatment to obtain the main grid electrode silver paste.
[0027] Optionally, the microwave-ultrasound combined treatment includes the following parameters: microwave power is 100-200 W, ultrasonic power is 200-300 W, and treatment time is 10s-40s.
[0028] In a third aspect, the present application provides a battery, wherein the front paste used in the battery includes the high-conductivity main grid electrode silver paste described in any one embodiment of the first aspect.
[0029] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0030] The embodiment of the present application provides a highly conductive main gate electrode silver paste. By rationally designing the chemical composition of the main gate electrode silver paste, the [BiO3], [BiO6], [BO3], [BO4] units in the Bi-B-Zn glass interact with the [PO4], [VO2], and [VO3] groups in the PV-Zn glass. The [BiO3] and [BiO6] units can form cross-links with the [PO4] group through oxygen atoms to enhance the stability and strength of the network structure. The conductive polymer plays a role in enhancing the conductivity and bonding strength in the silver paste. At the same time, it can form a good interface with the silver particles to improve the stability and reliability of the conductive network. The silver conductive material is the main conductive component in the silver paste, and it has good conductivity and stability. The silver alloy conductive material plays a role in assisting conductivity and enhancing performance in the silver paste. Thereby improving the conductivity of the main gate electrode silver paste. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The accompanying drawings herein are incorporated in and constitute a part of the specification, illustrate embodiments consistent with the present application, and together with the description, are used to explain the principles of the present application.
[0032] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0033] Figure 1 A schematic flow chart of a method for preparing a highly conductive main gate electrode silver paste provided in an embodiment of the present application. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0035] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined. The meaning of "several" is one or more, unless otherwise clearly and specifically defined.
[0036] It should be noted that, in the present invention, words such as "exemplary" or "for example" are used to indicate examples, illustrations or descriptions. Any embodiment or design described as "exemplary" or "for example" in the present disclosure should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of words such as "exemplary" or "for example" is intended to present related concepts in a specific way.
[0037] In the present invention, "at least one" means one or more, and "plurality" means two or more. "And / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone, where A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, at least one of a, b or c can mean: a, b, c, the combination of a and b, the combination of a and c, the combination of b and c, or the combination of a, b and c, where a, b, c can be single or multiple.
[0038] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0039] In a first aspect, the present application provides a high-conductivity main gate electrode silver paste, which is composed of the following components by mass: 0.5 to 4 parts of glass material, 50 to 70 parts of silver conductive material, 10 to 30 parts of silver alloy conductive material, 1 to 3 parts of organic additive, 1 to 3 parts of conductive polymer, and 10 to 15 parts of organic carrier; wherein,
[0040] The glass material consists of a first glass material and a second glass material;
[0041] The first glass material is a Bi-B-Zn series lead-free low-temperature melting glass material;
[0042] The second glass material is a PV-Zn series lead-free low-temperature melting glass material.
[0043] The first glass material (Bi-B-Zn series lead-free low-temperature melting glass material) has a lower glass transition temperature, which is conducive to low-temperature sintering. At the same time, the Bi-B-Zn series glass can have good glass-forming properties and stability. The first glass material, as a sintering aid, helps the bonding between silver particles and improves the density and mechanical strength of the conductive layer. At the same time, the low-temperature sintering characteristics can reduce thermal damage to the substrate.
[0044] The second glass material (PV-Zn series lead-free low-temperature melting glass material) also has a low glass transition temperature and can have good thermal stability and amorphous state retention ability. The second glass material is similar to Bi-B-Zn series glass and is used as a sintering aid to improve the performance of the conductive layer. At the same time, the addition of PV-Zn series glass can further optimize the sintering characteristics and conductive properties of the silver paste.
[0045] Silver conductive material is the main conductive component in silver paste. It has good conductivity and stability and can effectively transmit current. In silver paste, the content and particle size distribution of silver conductive material have an important influence on the conductive performance.
[0046] Silver alloy conductive materials play a role in assisting conductivity and enhancing performance in silver paste. By adding an appropriate amount of silver alloy conductive materials, the conductivity and heat resistance of the silver paste can be further improved while reducing costs.
[0047] Conductive polymer plays a role in enhancing the conductivity and bonding strength in silver paste. It can form a good interface with silver particles and improve the stability and reliability of the conductive network.
[0048] Organic additives play a major role in dispersing, wetting and stabilizing silver pastes. They can improve the dispersibility and fluidity of silver pastes, making the silver particles more evenly distributed on the substrate, thereby improving the conductivity.
[0049] Organic carriers include polymer resins and organic solvents, which can adjust the viscosity and fluidity of silver paste to ensure that the silver paste maintains proper performance during the printing process. At the same time, the polymer resin is also responsible for fixing the silver particles on the substrate.
[0050] In some embodiments, the mass ratio of the Bi-B-Zn based lead-free low temperature melting glass material to the PV-Zn based lead-free low temperature melting glass material is (2-4):1.
[0051] The Bi-B-Zn series lead-free low-temperature melting glass material and the PV-Zn series lead-free low-temperature melting glass material both have a lower glass transition temperature, which allows the silver paste to be sintered at a lower temperature, helps to closely bond the silver particles, and improves the density and conductivity of the conductive layer, thereby reducing thermal damage to the substrate.
[0052] The [BiO3], [BiO6], [BO3], and [BO4] units in the Bi-B-Zn glass interact with the [PO4], [VO2], and [VO3] groups in the PV-Zn glass. The [BiO3] and [BiO6] units can form cross-links with the [PO4] group through oxygen atoms, enhancing the stability and strength of the network structure. At the same time, the [BO3] and [BO4] units can also interact with the [VO2] and [VO3] groups, further enriching the diversity of the network structure.
[0053] In addition, the two glass materials act as sintering aids to promote the sintering process between silver particles. During the sintering process, the glass materials melt and penetrate between the silver particles to form a continuous glass phase, thereby enhancing the bonding force between the silver particles.
[0054] In some embodiments, the Bi-B-Zn based lead-free low-temperature melting glass material consists of the following components, in molar percentage: Bi2O3: 20-30 mol.%, B2O3: 40-50 mol.%, ZnO: 2-6 mol.%, SiO2: 2-6 mol.%, Al2O3: 1-5 mol.%, NaBr: 1-5 mol.%, SnO2: 1-5 mol.%, CdO: 1-5 mol.%.
[0055] Bi2O3: Its main function is to lower the melting temperature of glass and form structural units such as [BiO3] and [BiO6]. Changes in these unit structures will affect the network structure of the glass, thereby affecting its performance. At the same time, a proper amount of Bi2O3 helps to form a stable glass structure and provide a good carrier for silver paste, but an excessive amount can lead to a loose glass structure and affect conductivity.
[0056] B2O3: It is one of the main oxides in glass formation, forming [BO3] and [BO4] structural units. It can improve the transparency and glossiness of glass and is beneficial to the conductivity of silver paste. At the same time, it interacts with Bi2O3 to jointly affect the network structure and performance of glass.
[0057] ZnO: It has little effect on the glass structure, but can improve the transparency and chemical stability of the glass. In silver paste, ZnO can act as a flux, which helps the sintering of silver particles and the formation of a conductive network.
[0058] SiO2: It is an important component in glass formation and can increase the hardness and chemical stability of glass. In silver paste, an appropriate amount of SiO2 helps to form a dense conductive network and improve conductivity.
[0059] Al2O3: It can improve the chemical stability and mechanical strength of glass. In silver paste, Al2O3 can act as a reinforcing agent and help form a stable conductive network.
[0060] NaBr: As a halide additive, it can lower the melting point of glass while improving the transparency and gloss of glass. In silver paste, NaBr can help the sintering of silver particles and optimize the conductive network.
[0061] SnO2: It is a conductive oxide that can form a good interface with silver particles and improve the conductivity of silver paste. In glass, SnO2 can also increase the refractive index and glossiness of glass.
[0062] CdO: It is a conductive oxide that can increase the refractive index and solubility of glass. In silver paste, CdO can play a similar role in enhancing conductivity.
[0063] In some embodiments, the PV-Zn-based lead-free low-temperature melting glass material consists of the following components, in molar percentage: H3PO4: 40-50 mol.%, V2O5: 5-10 mol%, ZnO: 20-30 mol.%, In2O3: 5-10 mol%, KCl: 1-5 mol.%, CaO: 1-5 mol.%, Ce2O3: 1-5 mol.%, Y2O3: 1-5 mol.%.
[0064] H3PO4: H3PO4 will decompose into P2O5 at high temperature. P2O5 forms a glass network structure with V2O5 and ZnO, which affects the melting point and stability of the glass. The phosphate structure can indirectly affect the conductivity of the silver paste by affecting the internal structure of the glass.
[0065] V2O5: V2O5 forms a chain vanadate structure in the glass network structure, reducing the degree of cross-linking of the glass network structure. An appropriate amount of V2O5 can lower the melting point of the glass, help the silver paste to sinter at low temperatures, and form a good conductive path.
[0066] ZnO: ZnO is a modifier in the glass network structure, which can change the network structure and performance of the glass. At the same time, the change of ZnO content has little effect on the glass structure, but the right amount of ZnO helps to lower the melting point of the glass and improve the stability. In the silver paste, ZnO can provide good ionic conductivity and enhance the conductive properties of the silver paste.
[0067] In2O3: In2O3 is a wide bandgap semiconductor material with good electron mobility and chemical stability. In silver paste, In2O3 can be used as a dopant to improve the conductivity and stability of silver paste.
[0068] KCl: KCl melts at high temperatures to form molten salts with good ionic conductivity. In silver paste, KCl can act as an electrolyte to promote ion migration and bonding between silver particles, thus improving the conductivity of the silver paste.
[0069] CaO, Ce2O3, Y2O3: These oxides act as network modifiers in glass and can change the network structure and properties of glass. They can also act as stabilizers to improve the chemical and thermal stability of glass. At the same time, in silver paste, these oxides can indirectly affect the conductivity of silver paste by affecting the structure and properties of glass.
[0070] In some embodiments, the silver alloy conductive material is composed of silver-coated nickel, silver-coated tungsten and silver-coated copper, and the mass ratio of the silver-coated nickel, the silver-coated tungsten and the silver-coated copper is (1-5):(1-5):(1-5).
[0071] Silver-clad nickel is a composite material with silver as the shell and nickel as the core. The addition of nickel significantly improves the hardness and wear resistance of the material while maintaining the conductivity of silver. At the same time, nickel also has good corrosion resistance and oxidation resistance, which helps to improve the stability of silver alloy conductive materials in harsh environments.
[0072] Silver-coated tungsten is a composite material with silver as the shell and tungsten as the core. Tungsten has an extremely high melting point and has good thermal stability and mechanical strength. Among silver alloy conductive materials, silver-coated tungsten can improve the overall thermal stability and mechanical strength while maintaining excellent conductivity.
[0073] Silver-clad copper is a composite material with silver as the shell and copper as the core. The conductivity of copper is second only to silver, and its cost is relatively low. The addition of silver-clad copper can effectively reduce the cost of silver alloy conductive materials while maintaining high conductivity.
[0074] The mass ratio of silver-coated nickel, silver-coated tungsten and silver-coated copper is limited to (1-5):(1-5):(1-5). Silver-coated nickel, silver-coated tungsten and silver-coated copper can complement each other to form a more stable and efficient conductive network. At the same time, silver-coated nickel, silver-coated tungsten and silver-coated copper can work together on the mechanical properties of the material to form a comprehensive performance of high strength, high hardness and high toughness. In addition, silver-coated nickel, silver-coated tungsten and silver-coated copper can work together on the thermal stability of the material, enabling it to maintain stable performance at high temperatures.
[0075] In some embodiments, the conductive polymer is composed of polyaniline, polypyrrole, polyethylene dioxythiophene, and polystyrene sulfonic acid, and the mass ratio of the polyaniline, the polypyrrole, the polyethylene dioxythiophene, and the polystyrene sulfonic acid is 1:(1-2):(2-4):(2-4).
[0076] Conductive polymers are a new type of material with excellent conductivity and processing properties, usually composed of polymer chains with large π-bond conjugated structures. The delocalized π electrons on these polymer chains can move freely on the chains, giving them conductivity. Adding conductive polymers to conductive silver paste can significantly enhance conductivity and form a more efficient conductive network.
[0077] First, the molecular chains of polyaniline, polypyrrole and PEDOT all contain aromatic ring structures, which can attract each other through π-π stacking to form a stable intermolecular structure. This stacking effect helps to enhance the interaction between molecular chains and improve the overall stability of the material. Secondly, the amino groups on the molecular chains of polyaniline and polypyrrole and the nitrogen atoms on the pyrrole ring can form hydrogen bonds with the sulfonic acid groups, hydroxyl groups and the like in other components. The formation of hydrogen bonds can further enhance the interaction between molecular chains and improve the mechanical strength and heat resistance of the material. Thirdly, the sulfonic acid groups on the polystyrene sulfonic acid molecular chains carry a negative charge and can form electrostatic interactions with the positively charged regions (such as incompletely doped nitrogen atoms) on the molecular chains of polyaniline, polypyrrole and PEDOT. This electrostatic interaction helps to stabilize the molecular structure and can affect the conductive properties of the material.
[0078] In some embodiments, the organic additive includes at least one of the following: a dispersant, a thickener, a coupling agent, a surfactant, a leveling agent, and a defoaming agent; wherein,
[0079] The dispersant is polyvinyl pyrrolidone;
[0080] The thickener is ethyl cellulose or nitrocellulose;
[0081] The coupling agent is a silane coupling agent;
[0082] The surfactant is lecithin;
[0083] The leveling agent is dibutyl phthalate;
[0084] The defoamer is an organosilicon defoamer.
[0085] Polyvinyl pyrrolidone interacts with the surface of particles through the hydrophilic groups in its molecular structure to form an adsorption film, which changes the hydrophilicity and lipophilicity of the particle surface. This adsorption film can wrap the particles and generate repulsion between the particles, thereby effectively preventing the aggregation and precipitation of the particles and achieving uniform dispersion of the particles. At the same time, PVP dispersant can also form a dense protective film on the surface of the particles, improve the stability of the particles, and prolong the stability time of the dispersion. In addition, PVP dispersant has a surface active effect, which can reduce the surface tension between particles and promote the dispersion and stability of particles in the solvent.
[0086] Both ethyl cellulose and nitrocellulose thicken by forming hydrogen bonds with water molecules. When they are added to water, the molecular chains form hydrogen bonds with the water molecules, and the resulting gel structure can fix the position of the water molecules, thereby increasing the viscosity and consistency of the solution.
[0087] The molecular structure of silane coupling agents contains functional groups that can react chemically with both inorganic and organic materials. Silane coupling agents form strong chemical bonds between inorganic and organic materials, thereby significantly improving the performance of composite materials.
[0088] Figure 1 A schematic flow chart of a method for preparing a highly conductive main gate electrode silver paste provided in an embodiment of the present application.
[0089] like Figure 1 As shown, the present application provides a method for preparing a high-conductivity main gate electrode silver paste according to any one of the embodiments of the first aspect, the method comprising the following steps:
[0090] S1, melting a first glass material and a second glass material to form a first glass liquid and a second glass liquid respectively;
[0091] S2, drying the first glass liquid and the second glass liquid respectively, and then processing them into a first glass material and a second glass material by using a jet milling process;
[0092] The jet milling process is an efficient pulverizing method that can ensure that the particle size of glass powder is uniform and fine.
[0093] S3, mixing the first glass material and the second glass material to obtain a glass material;
[0094] S4, mixing the glass material, the silver conductive material, the silver alloy conductive material, the organic additive and the organic carrier to obtain a blend;
[0095] S5, subjecting the blend to a microwave-ultrasound combined treatment to obtain the main grid electrode silver paste.
[0096] In some embodiments, the microwave-ultrasound combined treatment includes the following parameters: microwave power is 100-200 W, ultrasonic power is 200-300 W, and treatment time is 10s-40s.
[0097] Silver particles and glass powder in silver paste can form agglomerates during the preparation process, which will affect the dispersion and conductivity of silver paste. Microwave-ultrasound combined treatment can produce strong vibration and impact, effectively destroying these agglomerate structures and making silver particles and glass powder more evenly dispersed in the organic carrier.
[0098] The penetrating and heating properties of microwaves can rapidly heat up the interior of the blend, accelerating the thermal motion between molecules, thereby promoting the dispersion of silver particles and glass powder in the organic carrier. At the same time, the cavitation effect and micro-jet action of ultrasound can produce a strong stirring effect on a microscopic scale, further promoting the mixing and uniform distribution of the components.
[0099] Microwave-ultrasonic combined treatment can not only promote physical dispersion, but also trigger or accelerate certain chemical reactions, such as oxidation and reduction reactions on the surface of silver particles, and the interaction between glass powder and silver particles. These reactions help to enhance the internal structure and properties of silver paste, such as improving conductivity and corrosion resistance.
[0100] Through microwave-ultrasonic combined treatment, silver particles can be arranged more closely together to form more conductive channels, thereby improving the conductivity of silver paste. At the same time, microstructural changes that can be produced during the treatment process also help to improve conductivity, such as increasing the contact area between silver particles and reducing contact resistance.
[0101] Microwave-ultrasonic combined treatment can improve the coating properties of silver paste, making it easier to coat evenly on the substrate. This helps to improve the adhesion and coverage of the silver paste to the substrate, thereby further improving the performance and reliability of the device.
[0102] Based on a general inventive concept, the present application provides a battery, wherein the front paste used in the battery includes the high-conductivity main grid electrode silver paste described in any one embodiment of the first aspect.
[0103] In summary, the main grid electrode silver paste and preparation method thereof of the present application have the following significant advantages:
[0104] (1) Optimized glass material combination: By using two lead-free low-temperature melting glass materials, Bi-B-Zn and PV-Zn, low-temperature sintering characteristics are achieved, which helps to reduce thermal damage to the substrate. At the same time, the interaction between the two glass materials enhances the stability and strength of the network structure, further optimizing the sintering characteristics and conductive properties of the silver paste.
[0105] (2) Efficient conductive material ratio: The reasonable combination of silver conductive material and silver alloy conductive material not only improves the conductivity and heat resistance of silver paste, but also effectively reduces the cost. At the same time, the composite use of silver-coated nickel, silver-coated tungsten and silver-coated copper forms a more stable and efficient conductive network, improving the overall performance of the material.
[0106] (3) Innovative addition of conductive polymers: The addition of conductive polymers significantly enhances the conductivity of the silver paste and forms a more efficient conductive network. The synergistic effect of conductive polymers such as polyaniline, polypyrrole, polyethylene dioxythiophene and polystyrene sulfonic acid improves the stability and heat resistance of the material.
[0107] (4) Perfect organic additive system: The rational selection of organic additives such as dispersants, thickeners, coupling agents, surfactants, leveling agents and defoamers improves the dispersibility, fluidity and stability of the silver paste. These additives help to evenly distribute the silver particles on the substrate and improve the conductive properties.
[0108] (5) Advanced microwave-ultrasound combined treatment technology: Microwave-ultrasound combined treatment can effectively destroy the agglomeration structure of silver particles and glass powder, making them more evenly dispersed in the organic carrier. This technology promotes the mixing and uniform distribution of the components, improving the conductivity and corrosion resistance of the silver paste. At the same time, the synergistic effect of microwaves and ultrasound also triggers or accelerates certain chemical reactions, enhancing the internal structure and performance of the silver paste.
[0109] (6) Precise control of the preparation process: The conditions and parameters of each step are strictly controlled during the preparation process, such as the melting, drying and crushing of the glass material, and the microwave-ultrasonic combined treatment of the blend. These precise controls ensure the stability and consistency of the quality and performance of the silver paste.
[0110] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.
[0111] Example 1
[0112] This embodiment provides a high-conductivity main gate electrode silver paste, which is composed of the following components by mass: 2.5 parts of glass material, 60 parts of silver conductive material, 20 parts of silver alloy conductive material, 2 parts of organic additive, 2 parts of conductive polymer, and 13.5 parts of organic carrier; wherein,
[0113] The glass material consists of a first glass material and a second glass material;
[0114] The first glass material is a Bi-B-Zn series lead-free low-temperature melting glass material;
[0115] The second glass material is a PV-Zn series lead-free low-temperature melting glass material.
[0116] The mass ratio of the Bi-B-Zn series lead-free low-temperature melting glass material to the PV-Zn series lead-free low-temperature melting glass material is 3:1.
[0117] In terms of molar percentage, the Bi-B-Zn series lead-free low-temperature melting glass material consists of the following components: Bi2O3: 30 mol.%, B2O3: 50 mol.%, ZnO: 4 mol.%, SiO2: 4 mol.%, Al2O3: 3 mol.%, NaBr: 3 mol.%, SnO2: 3 mol.%, CdO: 3 mol.%.
[0118] In terms of molar percentage, the PV-Zn series lead-free low-temperature melting glass material consists of the following components: H3PO4: 47 mol.%, V2O5: 9 mol.%, ZnO: 26 mol.%, In2O3: 8 mol.%, KCl: 3 mol.%, CaO: 2 mol.%, Ce2O3: 2 mol.%, Y2O3: 3 mol.%.
[0119] The silver alloy conductive material is composed of silver-clad nickel (YF-NI420), silver-clad tungsten (AgW50) and silver-clad copper (YF-A625), and the mass ratio of the silver-clad nickel, the silver-clad tungsten and the silver-clad copper is 2:3:4.
[0120] The conductive polymer consists of polyaniline, polypyrrole, polyethylene dioxythiophene and polystyrene sulfonic acid, and the mass ratio of the polyaniline, the polypyrrole, the polyethylene dioxythiophene and the polystyrene sulfonic acid is 1:1:3:3.
[0121] The organic auxiliary agent is a dispersant, and the dispersant is polyvinyl pyrrolidone (model PVPK17).
[0122] The organic carrier is composed of an organic resin and an organic solvent, the mass ratio of the organic resin content to the organic solvent is 30:70, the organic solvent is diethylene glycol butyl ether acetate, and the organic resin is ethyl cellulose resin.
[0123] Based on the above-mentioned high-conductivity main gate electrode silver paste, this embodiment also provides a method for preparing a high-conductivity main gate electrode silver paste, the method comprising the following steps:
[0124] S11, mixing the first glass material and the second glass material in a mixer, respectively, and heating them in a high-temperature furnace to melt them at high temperature to form uniform glass liquid, thereby forming a first glass liquid and a second glass liquid respectively;
[0125] S21, extracting the first glass liquid and the second glass liquid with water, cooling and drying them respectively, crushing the dried glass materials, and polishing, grinding and grading the crushed glass materials with a jet mill to obtain a first glass material and a second glass material;
[0126] S31, mixing the first glass material and the second glass material to obtain a glass material;
[0127] S41, mixing the glass material, the silver conductive material, the silver alloy conductive material, the organic additive and the organic carrier to obtain a blend;
[0128] S51, subjecting the blend to a microwave-ultrasound combined treatment to obtain the main gate electrode silver paste.
[0129] The microwave-ultrasound combined treatment includes the following parameters: microwave power is 150W, ultrasonic power is 250W, and treatment time is 20s.
[0130] Example 2
[0131] This embodiment provides a high-conductivity main gate electrode silver paste, which is composed of the following components by mass: 4 parts of glass material, 50 parts of silver conductive material, 30 parts of silver alloy conductive material, 3 parts of organic additive, 3 parts of conductive polymer, and 10 parts of organic carrier; wherein,
[0132] The glass material consists of a first glass material and a second glass material;
[0133] The first glass material is a Bi-B-Zn series lead-free low-temperature melting glass material;
[0134] The second glass material is a PV-Zn series lead-free low-temperature melting glass material.
[0135] The mass ratio of the Bi-B-Zn series lead-free low-temperature melting glass material to the PV-Zn series lead-free low-temperature melting glass material is 2:1.
[0136] In terms of molar percentage, the Bi-B-Zn series lead-free low-temperature melting glass material consists of the following components: Bi2O3: 20 mol.%, B2O3: 50 mol.%, ZnO: 5 mol.%, SiO2: 5 mol.%, Al2O3: 5 mol.%, NaBr: 5 mol.%, SnO2: 5 mol.%, CdO: 5 mol.%.
[0137] In terms of molar percentage, the PV-Zn series lead-free low-temperature melting glass material consists of the following components: H3PO4: 40 mol.%, V2O5: 10 mol%, ZnO: 30 mol.%, In2O3: 10 mol%, KCl: 4 mol.%, CaO: 1 mol.%, Ce2O3: 1 mol.%, Y2O3: 4 mol.%.
[0138] The silver alloy conductive material consists of silver-coated nickel, silver-coated tungsten and silver-coated copper, and the mass ratio of the silver-coated nickel, the silver-coated tungsten and the silver-coated copper is 5:3:1.
[0139] The conductive polymer consists of polyaniline, polypyrrole, polyethylene dioxythiophene and polystyrene sulfonic acid, and the mass ratio of the polyaniline, the polypyrrole, the polyethylene dioxythiophene and the polystyrene sulfonic acid is 1:2:2:2.
[0140] The organic auxiliary agent is a dispersant and a coupling agent, the mass ratio of the dispersant to the coupling agent is 1:1, the dispersant is polyvinyl pyrrolidone (model PVPK17), and the coupling agent is KH550.
[0141] The organic carrier is composed of an organic resin and an organic solvent, the mass ratio of the organic resin content to the organic solvent is 25:75, the organic solvent is diethylene glycol butyl ether acetate, and the organic resin is ethyl cellulose resin.
[0142] Based on the above-mentioned high-conductivity main gate electrode silver paste, this embodiment also provides a method for preparing a high-conductivity main gate electrode silver paste, the method comprising the following steps:
[0143] S11, mixing the first glass material and the second glass material in a mixer, respectively, and heating them in a high-temperature furnace to melt them at high temperature to form uniform glass liquid, thereby forming a first glass liquid and a second glass liquid respectively;
[0144] S21, extracting the first glass liquid and the second glass liquid with water, cooling and drying them respectively, crushing the dried glass materials, and polishing, grinding and grading the crushed glass materials with a jet mill to obtain a first glass material and a second glass material;
[0145] S31, mixing the first glass material and the second glass material to obtain a glass material;
[0146] S41, mixing the glass material, the silver conductive material, the silver alloy conductive material, the organic additive and the organic carrier to obtain a blend;
[0147] S51, subjecting the blend to a microwave-ultrasound combined treatment to obtain the main gate electrode silver paste.
[0148] The microwave-ultrasound combined treatment includes the following parameters: microwave power is 200W, ultrasonic power is 300W, and treatment time is 10s.
[0149] Example 3
[0150] This embodiment provides a high-conductivity main gate electrode silver paste, which is composed of the following components by mass: 1 part of glass material, 70 parts of silver conductive material, 10 parts of silver alloy conductive material, 2 parts of organic additive, 2 parts of conductive polymer, and 15 parts of organic carrier; wherein,
[0151] The glass material consists of a first glass material and a second glass material;
[0152] The first glass material is a Bi-B-Zn series lead-free low-temperature melting glass material;
[0153] The second glass material is a PV-Zn series lead-free low-temperature melting glass material.
[0154] The mass ratio of the Bi-B-Zn series lead-free low-temperature melting glass material to the PV-Zn series lead-free low-temperature melting glass material is 4:1.
[0155] In terms of molar percentage, the Bi-B-Zn series lead-free low-temperature melting glass material consists of the following components: Bi2O3: 30 mol.%, B2O3: 40 mol.%, ZnO: 6 mol.%, SiO2: 4 mol.%, Al2O3: 5 mol.%, NaBr: 5 mol.%, SnO2: 5 mol.%, CdO: 5 mol.%.
[0156] In terms of molar percentage, the PV-Zn series lead-free low-temperature melting glass material consists of the following components: H3PO4: 40 mol.%, V2O5: 10 mol.%, ZnO: 30 mol.%, In2O3: 5 mol.%, KCl: 5 mol.%, CaO: 2 mol.%, Ce2O3: 3 mol.%, Y2O3: 5 mol.%.
[0157] The silver alloy conductive material consists of silver-coated nickel, silver-coated tungsten and silver-coated copper, and the mass ratio of the silver-coated nickel, the silver-coated tungsten and the silver-coated copper is 1:3:5.
[0158] The conductive polymer consists of polyaniline, polypyrrole, polyethylene dioxythiophene and polystyrene sulfonic acid, and the mass ratio of the polyaniline, the polypyrrole, the polyethylene dioxythiophene and the polystyrene sulfonic acid is 1:2:4:4.
[0159] The organic auxiliary agent is a dispersant, and the dispersant is polyvinyl pyrrolidone (model PVPK17).
[0160] The organic carrier is composed of an organic resin and an organic solvent, the mass ratio of the organic resin content to the organic solvent is 35:65, and the organic solvent is diethylene glycol butyl ether acetate.
[0161] Based on the above-mentioned high-conductivity main gate electrode silver paste, this embodiment also provides a method for preparing a high-conductivity main gate electrode silver paste, the method comprising the following steps:
[0162] S11, mixing the first glass material and the second glass material in a mixer, respectively, and heating them in a high-temperature furnace to melt them at high temperature to form uniform glass liquid, thereby forming a first glass liquid and a second glass liquid respectively;
[0163] S21, extracting the first glass liquid and the second glass liquid with water, cooling and drying them respectively, crushing the dried glass materials, and polishing, grinding and grading the crushed glass materials with a jet mill to obtain a first glass material and a second glass material;
[0164] S31, mixing the first glass material and the second glass material to obtain a glass material;
[0165] S41, mixing the glass material, the silver conductive material, the silver alloy conductive material, the organic additive and the organic carrier to obtain a blend;
[0166] S51, subjecting the blend to a microwave-ultrasound combined treatment to obtain the main gate electrode silver paste.
[0167] The microwave-ultrasound combined treatment includes the following parameters: microwave power is 100W, ultrasonic power is 200W, and treatment time is 40s.
[0168] Comparative Example 1
[0169] This comparative example is modified as follows based on Example 1:
[0170] The main grid electrode silver paste is composed of the following components in parts by mass: 2.5 parts of glass material, 80 parts of silver conductive material, 2 parts of organic additive, 2 parts of conductive polymer, and 13.5 parts of organic carrier.
[0171] Comparative Example 2
[0172] This comparative example is modified as follows based on Example 1:
[0173] No conductive polymer is added to the main gate electrode silver paste.
[0174] Comparative Example 3
[0175] This comparative example is modified as follows based on Example 1:
[0176] The glass material is only the first glass material.
[0177] Comparative Example 4
[0178] This comparative example is modified as follows based on Example 1:
[0179] The glass material is only the second glass material.
[0180] Comparative Example 5
[0181] This comparative example is modified as follows based on Example 1:
[0182] In step S51, no microwave-ultrasound combined treatment is performed.
[0183] The present invention tests the performance of the main gate electrode silver paste prepared in Examples 1 to 3 and Comparative Examples 1 to 5. The specific testing method is as follows. The test results are shown in Table 1.
[0184] Viscosity: The Mars40 dynamic shear rheometer DV2T mode was used with a temperature control of 25°C to test the viscosity of the slurry;
[0185] Resistivity after curing: Print the fixed pattern of the test piece, measure the resistance value after curing (0.6×60mm), and calculate the resistivity according to the formula R=ρ·L / S;
[0186] Welding tensile force: Use 0.35mm tin-coated solder strip to weld the front and back main grid electrodes of the battery at 360℃, and use a tensile testing machine to perform tensile test.
[0187] Table 1 Performance of main grid electrode silver paste
[0188]
[0189] As shown in Table 1, the viscosity of the main gate electrode silver paste of Examples 1 to 3 is 175 to 185 Pa˙s, and the conductivity is 8.0 to 8.5×10 -6 Ωcm, welding tension is 2.5~3.0N / mm.
[0190] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A high-conductivity main gate electrode silver paste, characterized in that: The main grid electrode silver paste is composed of the following components by mass: 0.5 to 4 parts of glass material, 50 to 70 parts of silver conductive material, 10 to 30 parts of silver alloy conductive material, 1 to 3 parts of organic additive, 1 to 3 parts of conductive polymer, and 10 to 15 parts of organic carrier; wherein, The glass material consists of a first glass material and a second glass material; The first glass material is a Bi-B-Zn series lead-free low-temperature melting glass material; The second glass material is a PV-Zn series lead-free low-temperature melting glass material.
2. The high-conductivity main gate electrode silver paste according to claim 1, characterized in that: The mass ratio of the Bi-B-Zn series lead-free low-temperature melting glass material to the PV-Zn series lead-free low-temperature melting glass material is (2-4):
1.
3. The high-conductivity main gate electrode silver paste according to claim 2, characterized in that: In terms of molar percentage, the Bi-B-Zn based lead-free low-temperature melting glass material consists of the following components: Bi2O3: 20-30 mol.%, B2O3: 40-50 mol.%, ZnO: 2-6 mol.%, SiO2: 2-6 mol.%, Al2O3: 1-5 mol.%, NaBr: 1-5 mol.%, SnO2: 1-5 mol.%, CdO: 1-5 mol.%.
4. The high-conductivity main gate electrode silver paste according to claim 2, characterized in that: In terms of molar percentage, the PV-Zn series lead-free low-temperature melting glass material consists of the following components: H3PO4: 40-50 mol.%, V2O5: 5-10 mol%, ZnO: 20-30 mol.%, In2O3: 5-10 mol%, KCl: 1-5 mol.%, CaO: 1-5 mol.%, Ce2O3: 1-5 mol.%, Y2O3: 1-5 mol.%.
5. The high-conductivity main gate electrode silver paste according to claim 1, characterized in that: The silver alloy conductive material is composed of silver-coated nickel, silver-coated tungsten and silver-coated copper, and the mass ratio of the silver-coated nickel, the silver-coated tungsten and the silver-coated copper is (1-5):(1-5):(1-5).
6. The high-conductivity main gate electrode silver paste according to claim 5, characterized in that: The conductive polymer is composed of polyaniline, polypyrrole, polyethylene dioxythiophene and polystyrene sulfonic acid, and the mass ratio of the polyaniline, the polypyrrole, the polyethylene dioxythiophene and the polystyrene sulfonic acid is 1:(1-2):(2-4):(2-4).
7. The high-conductivity main gate electrode silver paste according to claim 1, characterized in that: The organic additives include at least one of the following: a dispersant, a thickener, a coupling agent, a surfactant, a leveling agent and a defoamer; wherein: The dispersant is polyvinyl pyrrolidone; The thickener is ethyl cellulose or nitrocellulose; The coupling agent is a silane coupling agent; The surfactant is lecithin; The leveling agent is dibutyl phthalate; The defoamer is an organosilicon defoamer.
8. A method for preparing a high-conductivity main gate electrode silver paste according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: S1, melting a first glass material and a second glass material to form a first glass liquid and a second glass liquid respectively; S2, drying the first glass liquid and the second glass liquid respectively, and then processing them into a first glass material and a second glass material by using a jet milling process; S3, mixing the first glass material and the second glass material to obtain a glass material; S4, mixing the glass material, the silver conductive material, the silver alloy conductive material, the organic additive and the organic carrier to obtain a blend; S5, subjecting the blend to a microwave-ultrasound combined treatment to obtain the main grid electrode silver paste.
9. The method for preparing a high-conductivity main gate electrode silver paste according to claim 8, characterized in that: The microwave-ultrasound combined treatment includes the following parameters: microwave power is 100-200W, ultrasonic power is 200-300W, and treatment time is 10s-40s.
10. A battery, characterized in that: The front paste used in the battery includes the high-conductivity main grid electrode silver paste according to any one of claims 1 to 7.
Citation Information
Patent Citations
Positive conductive silver paste of silicon solar cell and preparation method of positive conductive silver paste
CN105097071A
Lead-free low-temperature sintering conductive silver paste and preparation method and application thereof
CN110217998A
Titanate-based lead-free silver electrode paste, preparation method and use method thereof
CN111564234A
Front fine grid slurry of TOPCon battery, electrode and preparation method of front fine grid slurry
CN118448084A
Conductive paste and method for producing the same, and method for producing solar cell
JP2018041663A
Cited By
Base metal main grid slurry, preparation method thereof and photovoltaic cell
CN121237480A
Silver-tungsten double-shell copper-clad powder, preparation method thereof and conductive paste
CN122050908A